Is ambulance telephone triage using advanced medical priority dispatch protocols able to identify patients with acute stroke correctly?. Issue 6 (22nd May 2009) - Deakin, C D; Alasaad, M; King, P; Thompson, F
Abstract : Background and Purpose: As many as half the patients presenting with acute stroke access medical care through the ambulance service. In order to identify and triage these patients effectively as life-threatening emergencies, telephone-based ambulance software must have high sensitivity and specificity when using verbal descriptions to identify such patients. Software-based clinical coding was compared with the patient's final clinical diagnosis for all patients admitted by ambulance to North Hampshire Hospital (NHH) emergency department (ED) over a 6-month period to establish the ability of telephone-based triage to identify patients with likely stroke accurately. Methods: All emergency calls to South Central Ambulance Service over a 6-month period resulting in a patient being taken to NHH ED were reviewed. The classification allocated to the patient by ambulance advanced medical priority dispatch software (AMPDS version 11.1) was compared with the final clinical diagnosis made by a doctor in the ED. Results: 4810 patients were admitted to NHH during the study period. Of these, 126 patients were subsequently diagnosed as having had a stroke. The sensitivity of AMPDS software for detecting stroke in this sample was 47.62%, specificity was 98.68%, positive predictive value was 0.49 and negative predictive value was 0.986. Conclusions: Fewer than half of all patients with acute stroke were identified using telephone triage on the initial emergency call to the ambulance service. Less than one quarter received the highest priority of ambulance response. This first link in the chain of survival needs strengthening in order to provide prompt and timely emergency care for these patients.